Partial discharge measurement and modelling within an artificial cylindrical-shaped insulation under non-uniform electric field / Mohsin Ali Tunio - Mohsin Ali , Tunio (2016)
In the presence of void in cable insulation, repetition of partial discharge (PD) occurrences is one of the main sources of insulation degradation, which may lead to complete breakdown. Therefore, it is important to monitor the condition of cable insulation through PD measurement. Replicating PD measurement on a test object with a shape similar to power cable insulation geometry may help a better understanding of PD characteristics within cable insulation to be achieved. Therefore, in this work, test samples of cylindrical insulation-shaped material containing an artificial void were prepared in the laboratory for PD experiments. PD measurements on test specimens containing an artificial void within cylindrical insulation-shaped geometry for various amplitude, frequency and waveshape of the applied voltage, void sizes and temperature of the insulation material were performed. A physical model of PD activities within an artificial void in void in cylindrical insulation-shaped geometry was also proposed using Finite Element Analysis method and MATLAB. The advantage of this model over the previously reported models is this model can be used for simulation of PDs within a non-uniform electric field distribution in a void. The model was applied for simulation of PDs within the void in cylindrical insulation-shaped geometry to increase the understanding on PD physical phenomena through comparison with the measurement results. PD model parameters related to electron generation rate were determined using an optimisation method, the particle swarm optimisation (PSO). Comparison between the simulation and measurement results has managed to reveal the important parameters affecting PD phenomena within a void having non-uniform distribution of the electric field. These include distribution of charges on the void wall, decay rate of charges by surface conduction, inception field, extinction field and electron generate rate through surface emission and volume ionisation.